Postharvest physicochemical aspects of Campomanesia lineatifolia R. & P. fruit, a Myrtaceae with commercial potential - Balaguera-López, Helber Enrique; Fischer, Gerhard; Herrera-Arévalo, Aníbal (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Champa (Campomanesia lineatifolia R. & P) is a fruit with an exquisite taste and pleasant aroma, with high commercial potential because its flavor and nutritional composition, but it is highly perishable, and various aspects of its physiology are still unknown. The objective was to study the behavior of champa fruit during postharvest. Fruit were collected directly from trees when they were 100% yellow; then, they were stored at 22°C and 80% relative humidity. The variables were measured over four days. The fruit presented a climacteric behavior with a drastic increase in respiration on the second day after harvest, accompanied by an increase in ethylene production. Firmness decreased continuously and reached values of 1.5±0.14 N at the end. Weight loss increased and was 7.88±0.45% on day 4. Soluble solids increased until climacteric and then decreased. The pH decreased, and the total acidity increased. The color index increased and reached a value of 2.12±0.80. The polygalacturonase activity increased until the third day and subsequently decreased. The activity of this enzyme was related to the loss of firmness. Citric acid was the predominant acid and increased continuously postharvest. In the end, malic and oxalic acid decreased, and succinic had a slight increase. The predominant sugar was sucrose, followed by fructose and glucose. Sucrose presented a high value (61.42±11.6 mg g-1 of fresh weight) on day 1 after harvest; this value decreased on the second day, remained stable on day 3, and then increased for day 4. Glucose and fructose had the lowest values on the first day, which increased in a representative way on day 2, stabilized on day 3, and again increased until day 4. At this point, they had the highest concentration with 24.75±0.71 mg g-1 for glucose and 42.22±0.96 mg g-1 for fructose. These results contribute to the understanding of the postharvest behavior of this species.